Resolving Goods Procurement Contract Disputes via Arbitration: An Analysis of the PT Ifani Dewi vs. DKI Jakarta Government Case - Khairunnisa, Amanda Shofwa; Azmina, Fayza; Gultom, Juniartha Gladys Naomi Magdalena (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Disputes in procurement contracts often arise due to differences in the interpretation of obligations or allegations of default by one of the parties. Arbitration is frequently chosen as an alternative dispute resolution mechanism because it is considered faster, confidential, and provides legal certainty compared to litigation in court. This study discusses the dispute between PT Ifani Dewi and the Regional Government of DKI Jakarta, which was resolved through the Indonesian National Board of Arbitration (BANI). The analysis was conducted using a normative juridical approach by examining Law Number 30 of 1999 on Arbitration and Alternative Dispute Resolution, as well as civil law provisions on contracts. The findings indicate that the arbitration clause contained in the procurement contract is binding on the parties in accordance with the principle of pacta sunt servanda. The arbitration process in this case covered the registration of the dispute, the formation of the tribunal, the examination of the case, and the issuance of an award that is final and binding. Arbitration has proven to offer time efficiency, confidentiality, and legal certainty, although it has certain drawbacks, such as relatively high costs and the absence of appellate remedies. Therefore, arbitration can be regarded as an effective dispute resolution forum, particularly for strategic procurement contracts involving local governments.